Honey bee waggle dances facilitate shorter foraging distances and increased foraging aggregation. (April 2023) - Shackleton, Kyle; Balfour, Nicholas J.; Al Toufailia, Hasan; James, Emma; Ratnieks, Francis L.W.
Abstract : Many social organisms assist their group mates in foraging. The honey bee waggle dance allows nestmates to communicate the locations of rewarding flower patches. This remarkable behaviour can increase colony food collection under certain environmental conditions. However, we know little about how it affects colony foraging distribution in the landscape. Here, we predicted that dance communication influences foraging distances and increases the aggregation of foraging locations. We tested these predictions by manipulating the ability of Apis mellifera colonies situated in a heterogeneous landscape to communicate location information. Following established methodology, six study colonies in observation hives were turned horizontally and exposed to light treatments that produced either oriented or disoriented dancing. After 10–17 days, hives were then turned vertically and allowed to dance under normal conditions. We videoed and decoded dances to compare foraging patterns that had developed during the preceding treatment. This procedure was repeated throughout the foraging season from spring to autumn. Dance decoding revealed that, on average, bees from disoriented colonies recruited for food sources further away than oriented colonies. This effect was consistent throughout the year. Oriented colonies' recruitment was to a smaller area and was more spatially aggregated than that of disoriented colonies. However, experimental treatment did not affect colony weight gain. Our results show that dance communication plays an important role in the spatial distribution of foraging and is potentially beneficial in reducing commuting costs by directing recruits to closer foraging locations. These findings may be particularly relevant in heterogeneous landscapes. Highlights: The honey bee waggle dance enables recruitment to smaller foraging areas. Colonies unable to communicate dance information foraged further from their hives. The waggle dance is potentially beneficial in reducing commuting costs. These findings may be particularly relevant in heterogeneous landscapes.